A structural equation model of impulse buying behaviour in grocery retailing. (May 2017) - Bellini, Silvia; Cardinali, Maria Grazia; Grandi, Benedetta
Abstract: Purpose: Environmental changes, specifically the economic crisis and the growing penetration of digital technologies, have produced significant changes in shopping habits designed to create new paradigms for impulse buying behaviour. A new scenario seems to be opening up where customers enter the store much more prepared than in the past searching for products they had planned to buy. The purpose of this paper is to explore the determinants of impulse buying in a context of more planning and preparation for shopping. Design /methodology/approach: The data were obtained using a structured questionnaire from 316 respondents interviewed instore thanks to the cooperation of a leading Italian retail chain. We conducted a two-stage approach mall-intercept survey method to collect data. Firstly, we interviewed customers before entering the store, enquiring them about the pre-shopping preparation and shopping enjoyment tendency. Secondly, we interviewed the same customers at the end of their shopping trips, asking them to indicate which purchases were unplanned. Then, shoppers answered to questions regarding their general tendency to engage in impulse buying, the urges experienced to make impulse purchases, the level of positive and negative affect experienced during the shopping trip. Findings: In the structural model tested with LISREL 8, we found that pre-shopping tendency influences directly impulse buying: confirming our hypotheses, a higher pre-shopping preparation lead to lower levels of impulse buying. Results also showed that the personality variables (shopping enjoyment tendency and impulse buying tendency) influenced impulse buying through positive affect and urge to purchase. Our research did not find support for the relationship between negative affect and urge. Finally, higher levels of urge to buy impulsively lead to higher levels of impulse buying Originality/value: From the review of past and recent literature, we have not found a model that considers the influence of pre-shopping tendency on impulse buying behaviour. This paper addresses this major gap in extant literature by including pre-shopping tendency among the individual characteristics (impulse buying tendency and shopping enjoyment tendency) taken into consideration by past contributions.